2013
DOI: 10.1111/jgs.12166
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Northern Manhattan Study Global Vascular Risk Score and Successful Aging

Abstract: Objectives To examine the association between successful aging without subsequent cognitive decline (SA-ND) and the Northern Manhattan Study (NOMAS) global vascular risk score (GVRS), which is predictive of stroke, MI, and vascular death. Design Prospective cohort study. Setting A stroke-free sample of Hispanic, black, and white participants living in the same community enrolled in an MRI substudy of NOMAS, a population-based prospective cohort study. Participants A cognitive screen was administered at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
1
15
0
1
Order By: Relevance
“…26 Examining the whole sample, larger TCV was not significantly associated with variability in cognitive performance in any domain after adjusting for age, sex, race/ethnicity, and education. Half the sample was above age 70, with an average of 10 years of education.…”
Section: Resultsmentioning
confidence: 85%
“…26 Examining the whole sample, larger TCV was not significantly associated with variability in cognitive performance in any domain after adjusting for age, sex, race/ethnicity, and education. Half the sample was above age 70, with an average of 10 years of education.…”
Section: Resultsmentioning
confidence: 85%
“…Given the increased prevalence of cardiovascular disease in African Americans relative to Whites (Go et al, 2014), it is possible that African Americans are experiencing a greater cognitive burden as a result of these risk factors (Kuo et al, 2005; Warsch et al, 2013). While this study controlled for self-reported general health, future work should use more specific cardiovascular health data (e.g., blood pressure, diabetes status, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Health factors, especially cardiovascular factors, have also been implicated as possible mechanisms for race differences in cognition (Morgan, Sims, & Whitfield, 2010; Harper & Alexander, 1990), particularly given evidence that African Americans have a higher prevalence of hypertension and other cardiovascular issues (Go et al, 2014). Cardiovascular risk factors do appear to be important predictors of cognitive functioning in both African Americans and White older adults (e.g., Beeri, Ravona-Springer, Silverman, & Haroutunian, 2009; Izquierdo-Porrera & Waldstein, 2002; Warsch et al, 2013; Yaffe et al, 2004). Additionally, when compared to White participants, African American participants showed a stronger negative relationship between blood pressure and cognition (Robbins, Elias, Elias, & Budge, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This was supported by the high short-term mortality comparable to those lacking AHA criteria ( Table 2). The average age of 83 of the cohort and proportion of mortality in 2010 (54.3 %) does not yet allow assessment of compression of morbidity, but the average age is nevertheless high as compared to many other studies on this topic [3,18,19]. Finally, the frequent use of drugs affecting vascular risk factors necessitates that also midlife risk factors are related to AHA.…”
Section: Discussionmentioning
confidence: 89%
“…This concept involves that it is possible to ''pack'' human suffering, disabilities and illnesses to a minimum period at the end of lifespan and thus expand the healthy life span. In rapidly aging societies, AHA is important from both individual and societal perspectives, but studies about this as a multi-dimensional phenomenon are still relatively few [13][14][15][16][17][18][19][20]. Long-term follow-up up until very old age is essential and many cohorts are yet approaching a stage where most participants are octogenarians and older.…”
Section: Introductionmentioning
confidence: 98%